In Silico ADMET and Docking Studies of Thiazolidinedione-acetic-acid Hybrids as Antidiabetics with Cardioprotection - Maji, Deepanwita; Samanta, Subir; Patil, Vaishali M. (Letters in Drug Design & Discovery, 2020)
Background: Type-2-diabetes mellitus is associated with many side effects affecting vital body organs, especially heart. Thiazolidinediones are potent antidiabetics. Studies have proven that amino-acids and peptides promote glucose transport, have antioxidant properties, and fewer side effects, thus we designed hybrids by combining amino-acid esters and peptide esters with 2, 4 thiazolidinedione acetic acid moiety which can act as antidiabetic agent with cardioprotection properties. Methodology: In vitro ADME, toxicity, and docking studies were performed using Qikprop3.1.OSIRIS, PROTOX (Prediction of Rodent Oral Toxicity), and FlexX 2.1.3, respectively. Results: All the designed molecules belong to three sub-series, i.e. 2, 4-dioxothiazolidine-5-acetic acid single amino acid hybrid methyl esters, 2, 4-dioxothiazolidine-5-acetic acid dipeptide hybrid methyl esters and 2, 4-dioxothiazolidine-5-acetic acid tripeptide hybrid methyl esters. All molecules were non-toxic. SSMA2, SSMA14, SSMA49, and SSDM50 showed good docking scores in 2PRG and 2UV4, respectively. Conclusion: The selected in silico studies helped to design hybrids with less toxicity, target specificity with dual activity as potential anti-diabetic and cardioprotective agents.
Keywords: flexX